PROFITABILITAS SEBAGAI PEMEDIASI FIRM SIZE, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP CORPORATE VALUE - Selvi Marlina; Dicky Arisudhana Arisudhana (Universitas Budi Luhur, 2022)
This study aims to determine the effect of firm size, capital structure, and liquidity on corporate value with profitability as an intervening variable. The population of this study includes all manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) as many as 65 companies in the 2017-2020 period. The sampling technique used in this study was purposive sampling, and 31 companies were obtained with a total of 124 data. The data used in this study is secondary data in the form of company financial statements obtained from the official website www.idx.co.id. The analytical method used is multiple linear regression analysis carried out with the help of SPSS version 20. Based on the results of data analysis, it is concluded that firm size has a negative effect on profitability, capital structure has a positive effect on profitability, liquidity has a negative effect on profitability, and firm size has a positive effect on corporate value, Capital Structure has a positive effect on corporate value, Liquidity has no effect on Profitability, Profitability has a negative effect on corporate value, and Profitability is able to mediate the effect of Firm Size, Capital Structure, and Liquidity on Corporate Value.